Role of cohesion in the formation of kink wave fronts in vibrofluidized granular materials. (March 2022) - Yue, Han; Yan, Huyue; Huang, Kai
Abstract: The formation of kink wave fronts (KWFs) in a quasi-two-dimensional granular system is investigated numerically with a focus on the role of cohesive interactions between individual particles. The cohesive particle–particle interaction is achieved through tuning the velocity-dependent coefficient of restitution, based on an analytical model introduced recently (Gollwitzer et al., 2012; Müller and Huang, 2016). A comparison with experimental results (Butzhammer et al., 2015) indicates that the threshold for the emergence of traveling KWFs matches the regime in which the center of mass height of the granular layers fluctuates with a period that triples the vibration period. Further comparisons between dry and wet granular dynamics reveal that KWFs are more pronounced in wet granular layers because of enhanced collective motion induced by cohesion. Highlights: Possible to use molecular dynamics simulation for wet granular pattern formation. Simulation successfully reproduces traveling kink wave fronts. Cohesion between particles leads to collective motion. Periodicity of collective motion triggers traveling kink wave fronts.